Interrelation Of Myth And Ritual In Svanetian Folk And Everyday Existence - Intskirveli, Eter (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2017)
The paper tries to deal with the issue of the origin of Svanetian folk ritual - Liuskhuari . In Svanetian folk it is connected to famous tale about congestion of Enguri and flooding Ushguli territory which was the revenge of Devi against Lamaria. This ritual precedes the beginning of mowing in Svanetian living style. The work analyses not only the relation of myth and ritual, but also, it explains the Christian base of pagan ritual according to this concrete example and Svanetian mythoritual system peculiarities.